MiR-21 binding site SNP within ITGAM associated with psoriasis susceptibility in women - Hruska, Pavel; Kuruczova, Daniela; Vasku, Vladimir; Bienertova-Vasku, Julie (PLoS One, 2019)
BACKGROUND: Great progress has been made in the understanding of inflammatory processes in psoriasis. However, clarifying the role of genetic variability in processes regulating inflammation, including post-transcriptional regulation by microRNA (miRNA), remains a challenge. OBJECTIVES: We therefore investigated single nucleotide polymorphisms (SNPs) with a predicted change in the miRNA/mRNA interaction of genes involved in the psoriasis inflammatory processes. METHODS: Studied SNPs rs2910164 C/G-miR-146a, rs4597342 T/C-ITGAM, rs1368439 G/T-IL12B, rs1468488 C/T-IL17RA were selected using a bioinformatics analysis of psoriasis inflammation-associated genes. These SNPs were then genotyped using a large cohort of women with psoriasis (n = 241) and healthy controls (n = 516). RESULTS: No significant association with psoriasis was observed for rs2910164, rs1368439, and rs1468488 genotypes. However, the major allele T of rs4597342 -ITGAM was associated with approximately 28% higher risk for psoriasis in comparison to the patients with the C allele (OR = 1.28, 95% CI 1.01-1.61, p = 0.037). In case of genotypes, the effect of the T allele indicates the dominant model of disease penetrance as the CT and TT genotypes increase the chance of psoriasis up to 42% in comparison to CC homozygotes of rs4597342 (OR = 1.42, 95% CI = 1.05-1.94, p = 0.025). CONCLUSION: SNP rs4597342 in 3'UTR of ITGAM influencing miR-21 binding may be considered a risk factor for psoriasis development. Upregulated miR-21 in psoriasis is likely to inhibit CD11b production in the case of the rs4597342 T allele which may lead to Mac-1 dysfunction, resulting in an aberrant function of innate immune cells and leading to the production of cytokines involved in psoriasis pathogenesis.
Keywords: CD11b Antigen; genetické asociační studie; MicroRNAs; Genetic Predisposition to Disease; vazebná místa; Inflammation; Risk Factors; psoriáza; Genotype; Genetic Association Studies; mikro RNA; 3' nepřekládaná oblast; antigeny CD11b; jednonukleotidový polymorfismus; zánět; Binding Sites; Polymorphism, Single Nucleotide; lidé; Psoriasis; ženské pohlaví; Humans; rizikové faktory; 3' Untranslated Regions; genotyp; Alleles; Asian People; Female; Asijci; lidé středního věku; alely; genetická predispozice k nemoci; Middle Aged